2017
DOI: 10.1186/s12935-017-0431-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-34a and miR-206 act as novel prognostic and therapy biomarkers in cervical cancer

Abstract: BackgroundRecent evidence indicated that the aberrant expression of microRNA plays a crucial role in the development of cervical cancer. The overall shorter survival was strongly related to the abnormal expression of microRNA-34a (miR-34a) and microRNA-206 (miR-206), which target B cell lymphoma-2(Bcl2) and c-Met. Hepatocyte growth factor (HGF)/c-Met pathway is related to the occurrence, development and prognosis of cervical cancer, and c-Met is significantly overexpressed in cervical squamous cell carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 48 publications
(44 reference statements)
3
33
0
2
Order By: Relevance
“…It is negatively associated with lymph node metastasis and advanced FIGO stage, having the potential of being used as a prognostic biomarker [143][144][145]. miR-34a and miR-206 could also be possible prognostic instruments as their low expression in cervical cancer was linked to late stage disease, lymph node dissemination, and low survival rates [165].…”
Section: Mirnas In Cervical Cancermentioning
confidence: 99%
“…It is negatively associated with lymph node metastasis and advanced FIGO stage, having the potential of being used as a prognostic biomarker [143][144][145]. miR-34a and miR-206 could also be possible prognostic instruments as their low expression in cervical cancer was linked to late stage disease, lymph node dissemination, and low survival rates [165].…”
Section: Mirnas In Cervical Cancermentioning
confidence: 99%
“…MicroRNA-34a has attracted interest recently because of its ability to modulate a myriad of oncogenic functions in different cancers [21][22][23][24][25][26][27]. Not only does it play a role in cancer metastasis [28,29] and drug resistance [30], it is now being evaluated as a diagnostic as well as a prognostic biomarker [31][32][33]. In addition, a miR-34a inhibitor has been identified that may effectively protect against sevoflurane-induced hippocampal apoptosis by targeting Wnt1 and activating the Wnt/β-catenin pathway [34].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies have also shown that miR-206, a tumor suppressor miRNA that targets several oncogenes, was under expressed in many tumors [16-20], miR-206 inhibited cell proliferation, invasion and/or apoptosis by targeting SOX9 in lung cancer [16], Tbx3 in breast cancer [18], CDK9 in hepatocellular carcinoma [19], HDAC6in head and neck squamous cell carcinoma [20], ANXA2 in osteosarcoma [21], Bcl-2 in colorectal cancer [29], CXCL11 in prostate cancer [30], HDAC6 in squamous cell carcinoma [27], and cell metastasis by targeting MKL1/IL11 in breast cancer [17], FMNL2 in colorectal cancer [31], CXCL11 in prostate cancer [30]. And serum miR-206 might serve as a diagnostic biomarker in cancers, such as gastric cancer [32], renal cell carcinoma [33], also as a novel prognostic and therapeutics in cervical cancer [34]. In the study, we showed that inhibition of KIF2A by miR-206 decreased ovarian cancer cells A2780 and SKOV3 proliferation, migration and invasion and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%